(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: This study aimed to describe the moral sensitivity level and associated factors among Specialist Level I (CKI) nursing students. Methods: A cross-sectional descriptive study was conducted on 317 CKI nursing students at Nam Dinh University of Nursing in the 2022–2023 academic year. Data were collected using the Byrd’s Nurses Ethical Sensitivity Test with 10 clinical scenarios. An online survey was administered, and data were analyzed using descriptive and comparative statistics. Results: The mean moral sensitivity score was 21.91 ± 3.69 (scale 10–30). Of the participants, 65.6% were at the moderate level, 24.9% at the high level, and 9.5% at the low level. No significant differences in moral sensitivity were found by gender, type of undergraduate program, work position, workplace, age, or years of experience. Conclusion: CKI nursing students demonstrated mainly moderate moral sensitivity. These findings highlight the need to strengthen ethics education in postgraduate nursing programs, with special attention to those at low sensitivity levels.